Design, synthesis, linear and nonlinear photophysical properties of novel pyrimidine-based imidazole derivatives. (19th February 2016) - Zhang, Qiong; Luo, Lei; Xu, Hong; Hu, Zhangjun; Brommesson, Caroline; Wu, Jieying; Sun, Zhaoqi; Tian, Yupeng; Uvdal, Kajsa
Abstract : Novel pyrimidine imidazole derivatives with flexible ether chains have been synthesised and evaluated for their cell imaging performance via photophysical investigations and theoretical calculations. Abstract : Novel donor–π–acceptor (D–π–A) and donor–π–acceptor–π–donor (D–π–A–π–D) type pyrimidine imidazole derivatives with flexible ether chains (L1 andL2 ) have been efficiently synthesized through improved Knoevenagel condensation and Ullmann reactions with high yields. Based on systematic photophysical investigations and theoretical calculations, the structure–property relationships can be described as follows: (1) the linear and nonlinear optical properties of the target chromophores change regularly with increasing the number of branches and the polarity of the solvents. (2) The single-substituted chromophoreL2 exhibited a remarkable negative solvato-kinetic effect, while the double-substituted chromophoreL1 showed a positive solvato-kinetic effect. Significant bathochromic shifting of the emission spectra and larger Stokes shifts were observed in polar solvents. (3) The two-photon absorption (TPA) cross-section results further demonstrated that their TPA cross section values ( δ ) increase notably with increasing branch number, and the presence of high π-delocalization could induce large size-scalable TPA enhancements. (4) By comprehensively considering the optical performance, cytotoxicity and solubility, L1 was identified as the better candidate for living cell (HepG2) imaging.